The death factory : a Penn Cage novella - Iles, Greg (Iles, Greg. Penn Cage, 2014)
When a heart attack sends Penn's father, Tom Cage, to the ER, Tom begs that his son be brought to his side to hear a dying declaration. But when Penn arrives, Tom denies ever making the request - keeping his secrets for another day. The emergency hurls Penn back to a chilling case in Houston, where he worked in a DA's office known as the "death factory," which sent more killers to death row than any other in America. While Penn cares for his ailing wife, a tormented forensic technician brings him evidence of a crime lab in chaos, throwing past convictions into doubt and begging Penn to prevent an imminent travesty of justice. With the desperation of a man fighting death in his own home, Penn must find a way to bring the machinery of the death factory to a halt.